Maritime container terminal service quality in the face of COVID-19 outbreak - Charłampowicz, Jędrzej (Array, 2021)
The COVID-19 pandemic had a serious impact on global trade in 2020. The interruption of the supply chains due to various restrictions influenced the rapid drop in the transport demand. In the last decade, the global containerized trade has noted the growth of approximately 55,5%, with an average pace of growth of about 5% yearly. Container shipping, as one of the industries vulnerable to economic shocks, has noted a significant drop in trade. The role of maritime container terminals as an integrator and facilitator of global trade in the global supply chains is undisputed. Therefore, the role of services provided by the maritime container terminals has grown in importance. This situation generates the necessity to adapt to these circumstances in a way that expresses the need of improving the service quality, as one of the key aspects of competitiveness. The purpose of this paper is to determine the possibility to verify the relation between COVID-19 impacts on maritime container transport and maritime container terminal service quality. Based on the findings the suggested actions for service quality improvement are proposed.